2013
DOI: 10.1172/jci66125
|View full text |Cite
|
Sign up to set email alerts
|

PAR-1 contributes to the innate immune response during viral infection

Abstract: Coagulation is a host defense system that limits the spread of pathogens. Coagulation proteases, such as thrombin, also activate cells by cleaving PARs. In this study, we analyzed the role of PAR-1 in coxsackievirus B3-induced (CVB3-induced) myocarditis and influenza A infection. CVB3-infected Par1 -/-mice expressed reduced levels of IFN-β and CXCL10 during the early phase of infection compared with Par1 +/+ mice that resulted in higher viral loads and cardiac injury at day 8 after infection. Inhibition of eit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
233
4
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 138 publications
(248 citation statements)
references
References 94 publications
(138 reference statements)
10
233
4
1
Order By: Relevance
“…15 PAR1ko mice expressed lower levels of IFN-b and CXCL10 after infection and had higher levels of CVB3 in their hearts compared with WT mice. 15 The reduced IFN-b expression was associated with reduced NK cell infiltration into the heart in PAR1ko mice compared with WT controls. 15 In addition, we found that thrombin stimulation of WT murine splenocytes, but not PAR1ko cells, increased NK cell activity.…”
Section: Par1ko Mice Have Increased Cvb3-induced Myocarditismentioning
confidence: 94%
See 4 more Smart Citations
“…15 PAR1ko mice expressed lower levels of IFN-b and CXCL10 after infection and had higher levels of CVB3 in their hearts compared with WT mice. 15 The reduced IFN-b expression was associated with reduced NK cell infiltration into the heart in PAR1ko mice compared with WT controls. 15 In addition, we found that thrombin stimulation of WT murine splenocytes, but not PAR1ko cells, increased NK cell activity.…”
Section: Par1ko Mice Have Increased Cvb3-induced Myocarditismentioning
confidence: 94%
“…27,28 HSV may activate the clotting system to coat virally infected cells with fibrin to reduce their recognition and killing by NK cells and phagocytes. 15,29 Interestingly, Sutherland and colleagues found that activation of PAR1 and PAR2 increases HSV infection of endothelial cells in vitro (Figure 1). 26,30 Recently, this group analyzed the role of TF in HSV1 infection in mice.…”
Section: 25mentioning
confidence: 99%
See 3 more Smart Citations